An epidemiological study on assessment of Diabetes risk and determinants among adult population in urban area of Diphu, Assam - Baruah, Chetanjit; Begum, Tazkira; Boruah, Beeva (Indian Journal of Community Health, 2024)
Introduction: India is known as capital of Diabetes all over the world. Diabetes is a lifestyle disease which affects all age groups. Objective: To identify the risk of developing Diabetes in adults using Indian Diabetes Risk Score (IDRS) and identify associated factors. Material & Methods: A cross sectional study was done among 200 adults who were non-diabetic by systematic random sampling in urban area, Diphu, Assam using pre-designed semi structured questionnaire, validated IDRS and anthropometric measurements. SPSS Version 20.0 was used for data analysis. Predictors of risk of Diabetes was identified by logistic regression. Results: Among 200 participants, moderate risk was found in 106 subjects and high risk was found in 71 subjects. On multiple regression analysis, age, marital status, education, fruit consumption, blood pressure, Body mass index and physical activity were significantly associated with risk of developing Diabetes. Conclusion: Individuals at risk of diabetes should be identified by screening so that appropriate interventions can be done to prevent/delay the onset of diabetes.